Distinct spatial distribution and roles of Kupffer cells and monocyte-derived macrophages in mouse acute liver injury - Flores Molina, Manuel; Abdelnabi, Mohamed N.; Mazouz, Sabrina; Villafranca-Baughman, Deborah; Trinh, Vincent Quoc-Huy; Muhammad, Shafi; Bédard, Nathalie; Osorio Laverde, David; Hassan, Ghada S.; Di Polo, Adriana; Shoukry, Naglaa H. (Frontiers in Immunology, 2022)
Macrophages are key regulators of inflammation and repair, but their heterogeneity and multiple roles in the liver are not fully understood. We aimed herein to map the intrahepatic macrophage populations and their function(s) during acute liver injury. We used flow cytometry, gene expression analysis, multiplex-immunofluorescence, 3D-reconstruction, and spatial image analysis to characterize the intrahepatic immune landscape in mice post-CCl4-induced acute liver injury during three distinct phases: necroinflammation, and early and late repair. We observed hepatocellular necrosis and a reduction in liver resident lymphocytes during necroinflammation accompanied by the infiltration of circulating myeloid cells and upregulation of inflammatory cytokines and pro-repair chemokines. These parameters returned to baseline levels during the repair phase. We identified resident CLEC4F+ Kupffer cells (KCs) and infiltrating IBA1+CLEC4F- monocyte-derived macrophages (MoMFs) as the main hepatic macrophage populations during this response to injury. While occupying most of the necrotic area, KCs and MoMFs exhibited distinctive kinetics, distribution and morphology at the site of injury. The necroinflammation phase was characterized by low levels of KCs and a remarkable invasion of MoMFs capable of phagocytosing necrotic hepatocytes, while opposite kinetics/distribution were observed during repair. During the early repair phase, KCs originating from the yolk-sac were restored, whereas MoMFs diminished gradually then dissipated during late repair. MoMFs interacted with hepatic stellate cells during the necroinflammatory and early repair phases, potentially modulating their activation state and influencing their fibrogenic and pro-repair functions that are critical for wound healing. Altogether, our study reveals novel and distinct spatial and temporal distribution of KCs and MoMFs and provides insights into their complementary roles during acute liver injury.